2001
DOI: 10.1177/1356336x010072005
|View full text |Cite
|
Sign up to set email alerts
|

Urban Teachersí Use of Productive and Reproductive Teaching Styles Within the Confines of the National Curriculum for Physical Education

Abstract: The main purpose of this study was to describe the teaching styles employed by a sample of 18 teachers working in an urban setting under the conditions of the first revision of the National Curriculum for Physical Education. A second purpose was to compare the teaching styles used by this urban sample of teachers with those employed by a rural sample we had studied previously. Two lessons taught by each teacher to pupils in Years 7, 8, or 9 during one summer term were videotaped and coded with the Instrument f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
1
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 10 publications
(11 reference statements)
2
58
1
7
Order By: Relevance
“…Analyses of change have run the gamut from top-down, national perspectives (Curtner-Smith, 1999;Curtner-Smith, Todorovich, McCaughtry, & Lacon, 2001), to state and school district-wide multilevel change (Rink & Mitchell, 2003), to the infl uences of teachersʼ beliefs and biographies (Curtner-Smith; Ennis, 1994;Fullan, 1991;Rovegno & Bandhauer, 1997b), social environment (Ennis;Rovegno & Bandhauer, 1997a), and political context (Lipman, 1997). The result is an understanding that change is a complex process that couples teachers, students, administrators, parents, instruction, curriculum, and political agendas.…”
mentioning
confidence: 99%
“…Analyses of change have run the gamut from top-down, national perspectives (Curtner-Smith, 1999;Curtner-Smith, Todorovich, McCaughtry, & Lacon, 2001), to state and school district-wide multilevel change (Rink & Mitchell, 2003), to the infl uences of teachersʼ beliefs and biographies (Curtner-Smith; Ennis, 1994;Fullan, 1991;Rovegno & Bandhauer, 1997b), social environment (Ennis;Rovegno & Bandhauer, 1997a), and political context (Lipman, 1997). The result is an understanding that change is a complex process that couples teachers, students, administrators, parents, instruction, curriculum, and political agendas.…”
mentioning
confidence: 99%
“…It firstly presents my understanding of AR as a research methodology and details the reasons why I felt that it was a suitable form of inquiry to adequately answer my thematic concerns (Lincoln and Guba 1985). Secondly it looks at Cooperative Learning, and its ability to deliver the more indirect and pupil-centred practice that I sought (Curtner-Smith et al 2001, Metzler 2005.…”
mentioning
confidence: 99%
“…Putman (1993) suggested that although pupils and education are changing, educators' instructional approaches have been slow to evolve. Curtner-Smith, Todorovich and Lacon (2001) hypothesized that in order to meet current pedagogical demands teachers would "need to shift from the exclusive use of direct, teacher-centred, or reproductive styles of teaching to employing more indirect, pupil-centred, or productive styles" (178).…”
mentioning
confidence: 99%
“…O espectro dos estilos de ensino sugere que existem dois estilos "puros" de ensino, sendo que num deles são os alunos que tomam as decisões e noutro é o professor que as toma (CURTNER-SMITH et al, 2001). No fundo, este tipo de centralização da tomada de decisão relaciona-se com o nível de liberdade e centralização do ensino no aluno, convergindo em dois grupos diferenciados de estilos de ensino (MORGAN; SPROULE; KINGSTON, 2005): a) estilos de ensino de reprodução, onde o professor toma as decisões e os alunos executam o solicitado pelo professor, com reduzido nível de autonomia por parte dos alunos; e b) estilos de ensino de produção, onde os alunos gradativamente se tornam responsáveis pela sua própria aprendizagem e onde o professor se afigura como um guia ou orientador.…”
Section: Adequação Dos Estilos De Ensino Ao Modelo Tgfuunclassified